2011
DOI: 10.1007/s11515-011-1154-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution of methanogens based on their metabolic facets

Abstract: The information provided by completely sequenced genomes of methanogens can yield insights into a deeper molecular understanding of evolutionary mechanisms. This review describes the advantages of using metabolic pathways to clarify evolutionary correlation of methanogens with archaea and prokaryotes. Metabolic trees can be used to highlight similarities in metabolic networks related to the biology of methanogens. Metabolic genes are among the most modular in the cell and their genes are expected to travel lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 90 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…Similar approach has already been reported for designing b-methylaspartate mutase [3] and formyltetrahydrofolate ligase [5] from the sequences of archaea [19]. Similar to that, we have not done any alternation in native amino acids position or replacing residues, and, thus, it is directly based on the conserved domain of metalloenzymes.…”
Section: Molecular Docking For Binding Energy Of Shccc and Cfnrh Consmentioning
confidence: 74%
“…Similar approach has already been reported for designing b-methylaspartate mutase [3] and formyltetrahydrofolate ligase [5] from the sequences of archaea [19]. Similar to that, we have not done any alternation in native amino acids position or replacing residues, and, thus, it is directly based on the conserved domain of metalloenzymes.…”
Section: Molecular Docking For Binding Energy Of Shccc and Cfnrh Consmentioning
confidence: 74%
“…CRISPR-CAS systems are actively involved in evolving adaptive immune systems of thermophiles against invading mobiloms (Chellapandi and Ranjani 2011;Chellapandi 2011;Shah et al 2013). Many viruses of crenarchaeota coexist in stable relationships with their hosts, suggested that CRISPR systems adopt a regulatory role by exhibiting limited levels of interference (Lillestøl et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Most metal ions enter cells by an energy dependent saturable process via specific or generic metal ion carriers or channels (Bubb and Lester 1991). Metal chelate complexes may also be transported across the plasma membrane via specialized carriers (Cunningham and Berti 1993;Chellapandi 2011).…”
Section: Introductionmentioning
confidence: 99%